The role of Zakat Chamber in Reducing Poverty in Sudan within the period 2018- 2020 - A case Study of South Dar fur State - Fatur, Hassan Ali Osman (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to measuring the role of Zakat Chamber in alleviating poverty in South Darfur State, and clarify whether the projects of Zakat has affected on livelihoods level and income of the poor people in the region. Descriptive Analytical method was used. The primary data was collected by using questionnaire as a main tool of data collection from poor who have been awarded productive projects during the period of study. A random sample consists of three hundred and thirty seven person was selected. Statistical method was used to analyze the data through using the Statistical Package of Social Sciences(SPSS). The study concluded to the many results, the most important one is the great role of Zakat Chamber in reducing poverty in the state due to the large spreading of Zakat awarded productive projects to the poor beneficiaries. Also the analysis proved by Chi Square indication of 0.05. reflected that there is an inverse relationship having a positive impact statistically between a Zakat Chamber projects and the decreasing of unemployment rate, improving of livelihood level and increasing of personal income in the state.of South Darfur. The study recommended that the necessity for a Zakat Chamber to put in its consideration the training program for beneficiaries in order to be well qualified for manageing their projects.
Keywords: role; personal income; liveilhood level; Alleviation; Poverty; Zakat Chamber